Inequalities for Certain Ratios Involving the \((p,k)\)-Analogue of the Gamma function - Nantomah, Kwara (Communications in Mathematics and Applications, 2016)
Recently, a \((p,k)\)-analogue of the classical Gamma function was introduced and investigated. In this paper, we establish some inequalities for certain ratios involving the new analogue. The method is based on the monotonicity properties of some functions associated the \((p,k)\)-Gamma function.